Improving mixing characteristics with a pitched tip in kneading elements in twin‐screw extrusion. Issue 4 (30th October 2017) - Nakayama, Yasuya; Takemitsu, Hiroki; Kajiwara, Toshihisa; Kimura, Koichi; Takeuchi, Takahide; Tomiyama, Hideki
Abstract : In twin‐screw extrusion, the geometry of a mixing element mainly determines the basic flow pattern, which eventually affects the mixing ability as well as the dispersive ability of the mixing element. The effects of geometrical modification, with both forward and backward pitched tips, of a conventional forward kneading disks element (FKD) in the pitched‐tip kneading disks element on the flow pattern and mixing characteristics are discussed. Numerical simulations of fully filled, nonisothermal polymer melt flow in the melt‐mixing zone were performed, and the flow pattern structure and the tracer trajectories were investigated. The pitched tips largely affect the inter‐disk fluid transport, which is mainly responsible for mixing. These changes in the local flow pattern are analyzed by the distribution of the strain‐rate state. The distribution of the finite‐time Lyapunov exponent reveals a large inhomogeneity of the mixing in FKD is suppressed both by the forward and backward tips. By the forward tips on FKD, the mixing ability is relatively suppressed compared to FKD, whereas for the backward tips on FKD, the mixing ability is enhanced while maintaining the same level of dispersion efficiency as FKD. From these results, the pitched tips on the conventional KD turn out to be effective at reducing the inhomogeneity of the mixing and tuning the overall mixing performance. © 2017 American Institute of Chemical Engineers AIChE J, 64: 1424–1434, 2018